Conformational thermodynamics guided structural reconstruction of biomolecular fragments. Issue 2 (10th December 2015) - Sikdar, Samapan; Chakrabarti, J.; Ghosh, Mahua
Abstract : Conformational thermodynamics compares the modeling protocols to identify the conformation of the missing region leading to a suitable model for metal ion free (apo) skeletal muscle Troponin C. Abstract : Computational prediction of structure for macromolecular fragments is a formidable challenge. Here we show that the differences in conformational thermodynamics, computed using the equilibrium distribution of dihedral angles from molecular dynamics simulation, can identify the better model for the missing residues in the metal ion free (apo) skeletal muscle Troponin C (TnC). We use the model to understand Troponin I interaction with calcium (Ca 2+ ) ion bound TnC. Our method to compare conformational thermodynamics between different models can be easily generalized to any macromolecule to understand the structure and function even if experimental structures are not resolved.